16 What's a Connected Barn and How Do We Use It?. (7th May 2021) - Ramirez, Brett
Abstract: Internet enabled swine facilities with smart controllers are forging the future directions of swine management, data analytics, and research. Today's smart controllers have capabilities far beyond just ventilation operation, they are sophisticated data acquisition and control systems with cloud-based platforms for data aggregation and visualization. This technology has promoted the concept of a connected barn – a facility with autonomous, real-time data capture, analysis, and decision making. Connected barns can monitor indoor environmental conditions, personnel traffic, ventilation function, power consumption, bin weights, weather, refrigerators, etc. This new abundance of customizable measurement options sampled at a high-resolution will fundamentally change swine production. There is often a general lack of information related to conditions/events the pigs experience inside a barn that impact short-/long-term productivity and provide context for interpreting conventional data. Information is now superimposable with other data streams and new relationships between, for example, pig activity, environment, feed intake, daily gain, water consumption, etc. can be discovered. This will enable new avenues in nutrition, health, genetics, technology, husbandry, and engineering because a unified data stream, across numerous spaces is possible. Connected barns provide the link between pigs, data, and their environment. While opportunities are limitless, several key challenges need addressing: representativeness and accuracy of data; diligent management of advanced technology; and cultivation of transdisciplinary knowledge to understand limitations and make thoughtful inquiries. A connected barn is no longer a future concept, but a tangible production system ripe with a myriad of opportunities that will shape the course of animal production.